(untitled) (BIRDEM Medical Journal, 2019)
Adrenal sarcomatoid carcinoma (ASC) are very rare and aggressive malignant tumors of adrenal glands containing both epithelial (carcinomatous) and mesenchymal (sarcomatous) components. ASC presents a diagnostic challenge due to its atypical symptoms and histological patterns which influence treatment.At the time of diagnosis, a large percentage of patients are already at the metastatic stage and succumb within a few months. Here, we report a case of functional sarcomatoid carcinoma in right adrenal gland in a 37-year-old female, who presented with new onset hypertension. The patient underwent right sided adrenalectomy and she was alive at the time of writing the current report.To the best of our knowledge, ASC reported in literature to date showed only few patient presented with endocrine hypersecretion and only one patient presented with both hypertension and endocrine dysfunction. So, our case is the rarest among the rare. Birdem Med J 2020; 10(1): 73-75